(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Brassinosteroids (BRs) are a plant steroid that acts at the micro level concentration. Homobrassinolide (HBL) effect in two variety of potato plant (kufri lalima and kufri sadabahar) under heavy metal Lead (Pb) stress, investigation focus on finding the optimal concentration against control (C1 and C2)of HBL employing eight different concentrations (0.1,0.5,1.0,2.0,4.0,6.0.8.0,10.00 ppm) through in screening and found out that kufri lalima, the effects of Pb on potato seedling growth and germination parameter were observed and result show that % of germination is high in lower concentrations 0.1 ppm, 0.5 ppm, and 4.0 ppm, while CVG is optimum in 1.0 ppm and 2.0 ppm.VI is optimum with 4.0 ppm. EI is high with lower concentration 0.1 ppm, 0.5ppm, 1.0 ppm and 2.0 ppm. RSG is optimum in 1.0 ppm, 2.0 ppm. SI is high in higher concentrations 4.0 ppm, 6.0 ppm, 8.0 ppm and 10 ppm, GI is optimum in 2.0ppm. In Kufri Sadabahar, the effects of Pb on potato seedling growth and germination parameter were observed and result show that the% of germination is high in 1.0ppm and 6.0ppm while CVG is same in 1.0 ppm and 2.0 ppm compared with C1 and C2 and high in 0.1ppm,0.5ppm.VI optimum in 2.0 ppm. EI is similar in 2.0 ppm concentration compared with C1. SI is high in higher concentrations 4.0 ppm, 6.0 ppm. GI is optimum in 1.0ppm.